Study on the Removal of Trace Organic Matter from Water by the Ozone-Activated Carbon (O₃-C) Process - Schuch, Jimmy; Silva, Philippe; Becerra, Sumaya (Journal of Green Energy and Environmental Engineering, 2025)
The Ozone-Activated Carbon (O₃-AC) process leverages the synergistic action of ozone oxidation and activated carbon adsorption to eliminate trace organic compounds from water, establishing itself as one of the most prevalent integrated technologies in advanced water treatment. In conventional O₃-AC systems, the activated carbon filter bed accumulates significant dissolved oxygen from ozone decomposition, along with adsorbed and concentrated organic constituents. Therefore, after a period of operation, a large number of microorganisms inevitably grow on the activated carbon surface, causing the activated carbon, which primarily functioned by adsorption, to eventually transform into biological activated carbon, and its adsorption capacity rapidly declines. To address these issues, this study combines ozone and activated carbon within the same reactor, forming an integrated Ozone-Activated Carbon (O₃/C) process. Through the contact oxidation effect of ozone on the activated carbon, it aims to maintain the adsorption capacity of the activated carbon on one hand, and achieve synchronous regeneration of the activated carbon on the other. This study used three organic compounds with different solubilities and biodegradabilities in water—phenol, Rhodamine B (RhB), and humic acid—as representative pollutants to investigate the removal efficiency of two different ozone-activated carbon combination processes for these three pollutants. The stability of the effluent quality under impacts such as changes in raw water concentration, before and after backwashing, and ozone interruption was observed. Finally, characterization techniques including Scanning Electron Microscopy (SEM), Brunauer–Emmett–Teller (BET) surface area and porosity analysis, and Fourier Transform Infrared Spectroscopy (FT-IR) were employed to examine alterations in the surface morphology of activated carbon following prolonged operation. These methods were used to assess the effect of ozone on the activated carbon structure and to investigate the operational mechanisms underlying ozone‑activated carbon catalytic oxidation and the simultaneous ozone‑mediated regeneration of activated carbon. Through comparative analysis of the operational results of the two processes, it was concluded that the effluent removal effects of phenol and RhB by the O₃/C process were superior to those of the O₃-C process, while the removal effects of humic acid, turbidity, ammonia nitrogen, and CODMnwere similar between the two processes. When the influent phenol concentration fluctuated and the influent pollutants were switched multiple times, the O₃/C process recovered stability more rapidly, indicating that the O₃/C process has better adaptability to changes in raw water pollutant types and more stable treatment performance. After backwashing the activated carbon layer, both combined processes could restore their average treatment efficiency to the pre-backwashing level. In the case of ozone interruption in the process, the O₃/C process maintained stability for a longer duration, indicating that the O₃/C process has good buffering capacity during treatment.